TRANSFORMASI FOLKLORE DHUKUTAN MENJADI FILM DOKUMENTER: SEBUAH INSPIRASI DI ERA INDUSTRI KREATIF - Asep Yudha Wirajaya (Jurnal Tradisi Lisan Nusantara, 2022)
Abstract: Dhukutan is one of the folklore treasures of the Lawu Highlands community which still exists and is commemorated to this day. So far, the Dhukutan folklore has been able to raise the name of the Nglurah area as a tourist destination with artifacts in the form of Menggung Temple and its rich flora as well as souvenirs for tourists. However, in the midst of the never-ending storm of the COVID-19 pandemic, the idea began to appear to package the traditional dhukutan ceremony into digital form. By packaging in a documentary film format, Dhukutan folklore is expected to be able to raise and introduce the local wisdom of the Tawangmangu community. Thus, packaging folklore into a documentary film will be a challenge for young creators and filmmakers. Given the steep and sloped shooting location. In addition, the Dhukutan ceremony itself takes 3 days and 4 nights. Of course, all of this needs to be carefully considered for the prospective producers who will handle the Dhukutan documentary. However, at least the presence of a Dhukutan documentary will enrich and give its color to the film industry in Indonesia.